Hermeneutic Studies of Historical Romanticism of Pajajaran and Siliwangi in Mamaos Cianjuran - Zainhani, Fadila Rahma (UPI, 2023)
This study uses romantic hermeneutic studies to determine the historical value contained in Mamaos Cianjuran. Mamos Cianjuran about Pajajaran and Siliwangi is a literary work that contains high artistic and cultural value. By using the theory of Hermenautics, the essence of writing the work can be obtained. The problems discussed in this study are studied through six methods, 1) place literary works as objects under study and position them as facts of ontology, 2) objectivize their structure, by analyzing the structural work of literature. 3) symbolization. 4) interpretation of symbols, associated with the process of creativity of literati in producing his work. 5) associating symbols with other disciplines to complement the interpretation. 6) the discovery of meaning or message that exists in the literary work. Based on the results of the study, Mamaos Cianjuran contains the author's fantasy about the heyday of Pajajaran and Siliwangi